EVOLVING MARKETING TACTICS: A CONTEMPORARY RESEARCH EXPLORATION - Hart, Eleanor (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
China's market is currently at a pivotal juncture, oscillating between the international and domestic markets. As the nation's market leans toward nationalization, the international market is progressively infiltrating China's landscape. In response, enterprises must adapt to the evolving dynamics of the international market, continually fine-tune their marketing strategies, prioritize consumers, and foster structured and positive growth. Marketing assumes a central role in guiding an enterprise's developmental journey, showcasing the enterprise's value, and particularly shining in the midst of intense market competition, yielding enhanced economic benefits. In the dawning era, the competition among enterprises intensifies, necessitating innovative marketing strategies to secure efficient and rational profits. This paper explores the ever-changing landscape of China's market, emphasizing the pivotal role of marketing in achieving economic success in an era marked by fierce competition.